(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
The need to train local development promoters capable of managing the processes and carrying out effective community investigations motivated us to carry out this investigation. The formation of investigative skills in the promoters, based on solid scientific criteria based on community work and the skills to be strengthened for their successful performance have been the basis of the proposal. The local development approaches in Cuba are assumed as particular transformation processes, the promoters must be able to responsibly assume the investigations and diagnoses to achieve an approach to the social reality and to his environment.